The effect of high [K(+)](o) on spontaneous Ca(2+) waves in freshly isolated interstitial cells of Cajal from the rabbit urethra - Drumm, Bernard T. (Wiley Periodicals, Inc., 2014)
Interstitial cells of Cajal (ICC) act as putative pacemaker cells in the rabbit urethra. Pacemaker activity in ICC results from spontaneous global Ca(2+) waves that can be increased in frequency by raising external [K(+)]. The purpose of this study was to elucidate the mechanism of this response. Intracellular [Ca(2+)] was measured in fluo‐4‐loaded smooth muscle cells (SMCs) and ICC using a Nipkow spinning disk confocal microscope. Increasing [K(+)](o) to 60 mmol/L caused an increase in [Ca(2+)](i) accompanied by contraction in SMCs. Raising [K(+)](o) did not cause contraction in ICC, but the frequency of firing of spontaneous calcium waves increased. Reducing [Ca(2+)](o) to 0 mmol/L abolished the response in both cell types. Nifedipine of 1 μmol/L blocked the response of SMC to high [K(+)](o), but did not affect the increase in firing in ICC. This latter effect was blocked by 30 μmol/L NiCl(2) but not by the T‐type Ca(2+) channel blocker mibefradil (300 nmol/L). However, inhibition of Ca(2+) influx via reverse‐mode sodium/calcium exchange (NCX) using either 1 μmol/L SEA0400 or 5 μmol/L KB‐R7943 did block the effect of high [K(+)](o) on ICC. These data suggest that high K(+) solution increases the frequency of calcium waves in ICC by increasing Ca(2+) influx through reverse‐mode NCX.